Bromocriptine inhibits proliferation in the endometrium from women with adenomyosis - Tang, Yiqun; Ponandai-srinivasan, Sakthivignesh; Frisendahl, Caroline; Andersson, Johanna K.; Pavone, Dora; Stewart, Elizabeth A.; Lalitkumar, Parameswaran Grace Luther; Korsching, Eberhard; Bogavarappu, Nageswara Rao; Gemzell-Danielsson, Kristina (Frontiers in Endocrinology, 2023)
Objective: Bromocriptine treatment has been shown to reduce menstrual bleeding and pain in women with adenomyosis in a pilot clinical trial. The underlying mechanism contributing to the treatment effect is however unknown. This study was to explore the effect of bromocriptine on the proliferation and migration properties of the endometrium in women with adenomyosis, by assessing cellular and molecular changes after six months of vaginal bromocriptine treatment. Methods: Endometrial specimens were collected during the proliferative phase from women with adenomyosis (n=6) before (baseline) and after six months of vaginal bromocriptine treatment. Immunohistochemistry was used to determine changes in the protein expression of Ki67 in the endometrium. Primary endometrial stromal cells isolated at baseline were expanded in vitro and exposed to different doses of bromocriptine to determine the optimal half-maximum inhibitory concentration (IC50) using CellTiter-Blue® Cell Viability Assay. Cell proliferation was assessed by bromodeoxyuridine ELISA assay and Ki67 gene expression was checked by real-time PCR. The migratory ability of endometrial stromal cells was determined by wound healing and transwell migration assays. Small RNA sequencing was applied on tissues collected from women with adenomyosis before and after bromocriptine treatment to identify differentially expressed micro RNAs. Bioinformatic methods were used for target gene prediction and the identification of biological pathways. Results: Vaginal bromocriptine treatment reduced the Ki67 protein expression in the endometrium of women with adenomyosis and did not change the prolactin mRNA expression and protein concentration of prolactin in endometrial tissues. Bromocriptine significantly inhibited the proliferative and migrative abilities of endometrial stromal cells derived from women with adenomyosis in vitro. Moreover, small RNA sequencing revealed 27 differentially expressed micro RNAs (miRNAs) between the endometrium of women with adenomyosis before and after six months of vaginal bromocriptine treatment. KEGG pathway analysis on targeted genes of 27 miRNAs showed that several signaling pathways associated with cell proliferation and apoptosis were enriched after treatment. Conclusion: Bromocriptine treatment exhibits an anti-proliferative effect in the endometrium of women with adenomyosis in vivo and in vitro. Bromocriptine might inhibit the proliferation of endometrial tissue in adenomyosis in part through the regulation of dysregulated microRNAs and proliferation-associated signaling pathways.